2011
DOI: 10.1111/j.1439-0507.2010.01920.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of human umbilical vein endothelial cells incubated with Cryptococcus neoformans var. neoformans

Abstract: Cryptococcus neoformans is a medically important fungus and can infect all the organs of the body. As vascular endothelial cell is an important target for C. neoformans to penetrate any organs, the differential protein expression of human umbilical vascular endothelial cell (HUVEC) after incubating with C. neoformans may be the key to penetration. The proteins of HUVECs incubated with C. neoformans and normal HUVECs were collected and purified. After two-dimensional electrophoresis, the differential protein ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
5
4
0
Order By: Relevance
“…This is consistent with the 3-fold increase in the expression of annexin A2 and the ϳ2-fold increase in S100A10, proteins involved in recruiting factors to the cytoskeleton (42). This notion is supported by previous results demonstrating that transmigration of C. neoformans often involves a transcellular process that is dependent on cytoskeleton rearrangement (16,43). Indeed, it has been shown that actin reorganization via the dephosphorylation of cofilin plays a significant role in the migration of cryptococci across the blood-brain barrier, and the downregulation of S100A10 in murine brain endothelial cells inhibited the internalization of cryptococci (16,43).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is consistent with the 3-fold increase in the expression of annexin A2 and the ϳ2-fold increase in S100A10, proteins involved in recruiting factors to the cytoskeleton (42). This notion is supported by previous results demonstrating that transmigration of C. neoformans often involves a transcellular process that is dependent on cytoskeleton rearrangement (16,43). Indeed, it has been shown that actin reorganization via the dephosphorylation of cofilin plays a significant role in the migration of cryptococci across the blood-brain barrier, and the downregulation of S100A10 in murine brain endothelial cells inhibited the internalization of cryptococci (16,43).…”
Section: Discussionsupporting
confidence: 89%
“…This notion is supported by previous results demonstrating that transmigration of C. neoformans often involves a transcellular process that is dependent on cytoskeleton rearrangement (16,43). Indeed, it has been shown that actin reorganization via the dephosphorylation of cofilin plays a significant role in the migration of cryptococci across the blood-brain barrier, and the downregulation of S100A10 in murine brain endothelial cells inhibited the internalization of cryptococci (16,43). Accordingly, we found that S100A10 was upregulated during both attachment and internalization, further suggesting that S100A10 facilitates the migration of C. neoformans across the human brain endothelium.…”
Section: Discussionsupporting
confidence: 80%
“…Cofilin-1 was identified in HUVEC monolayers after interaction with C. neoformans [84], and this protein was also identified in the present work, showing a higher abundance level in HUVECs challenged with Δugm1 [28]. Curiously, the proteomics study of the HUVEC response to C. neoformans suggested the modulation of proteins involved in oxidative stress [84], as shown in the present study for A. fumigatus.…”
Section: Studies Regarding Cryptococcus Neoformans Interaction With Esupporting
confidence: 83%
“…HBMECs [84,85]. It is known that the host cellular actin cytoskeleton undergoes extensive remodeling during pathogen invasion, and some studies have indicated that cofilin phosphorylation plays an important role in actin dynamics [86,87,88].…”
Section: Studies Regarding Cryptococcus Neoformans Interaction With Ementioning
confidence: 99%
See 1 more Smart Citation